FRAMING PUBLIC SANITATION: AN ANALYSIS OF NEWSPAPER COVERAGE OF PUBLIC SANITATION ISSUES IN REGIONAL NEWSPAPERS OF TAMIL NADU - Sudhan M, Mohana; Ramalingam, Subramani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Public sanitation remains an underexplored domain in Indian media coverage despite its significance to public health and development. This study examines how Tamil-language newspapers frame sanitation-related news. Using Entman's framing theory and agenda-setting principles, a content analysis was conducted on 186 news articles from three major regional newspapers. Findings reveal dominant reliance on responsibility and sensationalist frames with limited use of environmental or advocacy-oriented narratives. The research suggests a need for more constructive journalism, highlighting community voices and long-term policy implications.